2020
DOI: 10.1002/jae.2787
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from privileged peers? Evidence from siblings in schools

Abstract: By comparing siblings attending the same school at different points in time, we investigate whether the effect of peer quality on long-term labor market outcomes varies with parental background. We find that exposure to better peers-who have higher mean parental education-increases lifetime earnings of disadvantaged students, coming from families with low parental education, but penalizes privileged students from better educated families. These results suggest that desegregation policies that allocate disadvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…In addition, the Charlotte Mecklenburg Public School district has had a school choice program from 2002 so we exclude that district. 19 Bertoni, Brunello, and Cappellari (2020) use this design to study the effects of privileged peers.…”
Section: Additional Threats To Internal Validitymentioning
confidence: 99%
“…In addition, the Charlotte Mecklenburg Public School district has had a school choice program from 2002 so we exclude that district. 19 Bertoni, Brunello, and Cappellari (2020) use this design to study the effects of privileged peers.…”
Section: Additional Threats To Internal Validitymentioning
confidence: 99%
“…Additionally, the outflow of well-supported pupils worsens the socio-economic composition of local secondary schools. As a result, the efficiency of school allocation may worsen with non-linear peer effects, i.e., if disadvantaged pupils benefit from proximity with well-supported peers without harming the latter's achievement (Carrell et al, 2009;Bertoni et al, 2020a).…”
Section: The Meet the Parents Projectmentioning
confidence: 99%
“…The findings of the literature di↵er considerably: certain papers show that low-achieving students are harmed by HP peers, because of the changes in group interaction, while others reports that lower ability students are more a↵ected by higher quality peer exposure, suggesting that ability spillovers could be a potential channel driving these results students (Feld and Zölitz (2017); Cools et al (2019)). For example, Bertoni et al (2020) found that the exposure to better peers increases lifetime earnings of disadvantaged students, coming from families with low parental education, but penalizes privileged students from better educated families. Also Booij et al (2017) found that low ability students are mostly positively a↵ected, while HP students are completely una↵ected by changes in the ability composition of their peers.…”
Section: Heterogeneitymentioning
confidence: 99%